Experience of pemetrexed in maintenance therapy for metastatic lung adenocarcinoma - L. Yu. Vladimirova; A. E. Storozhakova; E. A. Kalabanova; P. N. Meshcheryakov; S. V. Oskin; S. N. Kabanov; N. Yu. Samaneva; Ya. V. Svetitskaya; A. V. Tishina (Южно-Российский онкологический журнал, 2021)
Lung cancer is among the most common malignant diseases in Russia. In 80–90%, its morphological type is nonsmall cell lung cancer. Stage IV primary advanced lung cancer is diagnosed in 41% of patients. Median overall survival in stage IV patients receiving chemotherapy is 7–12 months. Treatment for stage IV lung adenocarcinoma is based on predictive and prognostic factors. Chemotherapy, chemoimmunotherapy or immunotherapy is recommended in the absence of driver mutations in the EGFR (exons 19 and 21) and BRAF genes, ALK and ROS1 translocations.Platinum- based regimens are preferred as the fi rst-line chemotherapy. Stabilization, partial or complete response after 4–6 chemotherapy cycles allow for maintenance therapy with pemetrexed to increase progression-free survival and overall survival.Purpose of the study. Using a real clinical case, to confirm the efficacy of pemetrexed in the treatment for stage IV lung adenocarcinoma in the second-line therapy in combination with platinum- based agents and in a maintenance therapy.A clinical case of a patient with central cancer of the lower lobe of the right lung St IV (cT3N2M1) is presented; the first treatment stage involved 3 cycles of the fi rst-line polychemotherapy (paclitaxel 175 mg/m² intravenously on day 1, carboplatin AUC 5 intravenously on day 1, every 3 weeks), and 6 cycles of the second-line polychemotherapy (pemetrexed 500 mg/m2 intravenously on day 1, cisplatin 75 mg/m² intravenously on day 1 of the 21-day cycle). Stabilization of the disease was achieves, and 20 cycles of maintenance therapy with pemetrexed followed; the achieved effect persisted and was confirmed by spiral X-ray computed tomography every 3 months. The objective effect of anticancer therapy was assessed according to the RECIST 1.1 criteria. It took 20 months from the beginning of the second-line anticancer medical therapy to progression, and 16 months from the start of maintenance pemetrexed to progression. The safety profile was satisfactory, and the ECOG performance status 0 maintained. Only one adverse effect, degree I general weakness, was noted, which did not have a negative impact on the patient's quality of life.